Pelatihan Perakitan dan Pemograman Running Text Bagi Warga Binaan Lapas Permisan Nusa Kambangan Kabupaten Cilacap - Arif Sumardiono; Erna Alimudin; Saepul Rahmat; Hendi Purnata; Zaenurohman Zaenurohman (Politeknik Negeri Cilacap, 2021)
Penitentiary (LP) is a correctional facility in which there are assisted residents consisting of convicts. The social organization aims to ensure that its assisted residents are aware of the mistakes that have been made before and can improve themselves so that they do not fall into the same mistakes. In order to achieve this goal, the government has formulated the concept of structured guidance, training and empowerment in the field of religion or expertise for assisted residents so that they can have the ability after leaving the correctional institution. One of the well-known Penitentiary (LP) is in Cilacap Regency, precisely on the island of Nusa Kambangan. The penitentiary is called Lapas Permisan Nusa Kambangan. In this institution there are trainings for assisted residents so that after leaving the prison they can have business opportunities or get jobs to support their daily lives. One of them is training in making calligraphy in the form of figures, batik, etc. To make this happen. Therefore the Electrical Engineering Study Program will conduct training activities on how to assemble a dot matrix and its control devices to make running text and prayer time schedules. This activity is a positive alternative for the assisted residents, increasing the abilities and insights that will be used when they graduate as assisted residents or leave the Permisan Nusa Kambangan Prison. This training was held for 3 meetings with the preparation of modules and lesson plans to be adjusted.